Zjawisko sharentingu – między prawem do prywatności dziecka a aktywnością rodziców w mediach społecznościowych - Sobczak , Anna (Studia Edukacyjne, 2023)
The article is devoted to the phenomenon of sharenting, meaning the sharing of content about their children by parents on the internet. Its emergence is associated with the development and popularization of social media, which have become an integral part of the modern world. A part of society, especially young people, can see sharenting as one of the dimensions of modern parenting. On the other hand, the phenomenon of parents publishing children’s images and other information about them online has many potential negative consequences. The article presents the essence and scale of sharenting as well as its causes and consequences. The author attempted to answer the question: should sharenting be viewed in terms of a threat to children’s privacy or as one of the sides of modern parenting? The article points out that sharenting is one of the significant problems of the current reality, in which considerable activity of parents is observed in social media. It also suggests some measures that could reduce the negative effects of this phenomenon.